Dynamic design and analysis of subsea CO2 discharging flowline for cargo submarines used for CCS in low-carbon and renewable energy value chains - Dai, Tianjiao; Yang, Shuo; Xing, Yihan; Ma, Yucong (Frontiers in Marine Science, 2022)
Developing offshore low carbon and renewable energy value chains to realize a net-zero energy future requires combining offshore renewable energy and carbon capture storage (CCS) solutions. The subsea shuttle tanker (SST) was presented in recently published works to accelerate the adoption of offshore CCS systems. The SST is a novel underwater vessel designed to transport CO2 autonomously from offshore facilities to subsea wells for direct injection at marginal fields using a flowline connected. The SST will be subjected to stochastic currents and experience dynamic responses during this offloading process. The offloading flowline must be designed to handle this dynamic response. As such, this paper establishes the baseline design for this flowline. The cross-section and global configuration designs drive the flowline design. For the cross-section design, the pressure containment, collapse and local buckling criteria defined in DNV-OS-F101 are applied to validate the required structural capacity at specified water depths. For the configuration design, the principle factors concerning the water depth, internal flow rate, and current speed are investigated to further validate the stress capacity according to the allowed von Mises stress level for a more robust baseline design. Finally, the flowline connecting and disassembly methodology is proposed, and the critical factor of well-coordinated speed between flowline and SST is investigated to avoid overbending during the lifting and lowering phases.